The influence of calfhood diarrhea and pneumonia on preweaning growth and reproductive performance of Holstein heifers - Mely T. Olivera; Jesús Mellado; José E. García; Juan A. Encina; Perpetuo Álvarez; Ulises Macías-Cruz; Leonel Avendaño; Miguel Mellado (Spanish Journal of Agricultural Research)
Aim of the study: To determine the effect of diarrhea and pneumonia on preweaning weight gain and subsequent reproductive performance of Holstein heifers in a hot environment.